Adding antibacterial/antiviral properties to medical purpose materials by modification with silver and copper nanoparticles - A. V. Rudenko; L. D. Kisterska; O. B. Loginova; S. L. Rybalko; H. B. Solodukha; A. M. Pochynok (Хімія, фізика та технологія поверхні, 2025)
In modern times, especially during epidemics and pandemics, respiratory protection becomes especially important. One of the most effective means of protection against airborne infections such as influenza, SARS, and COVID-19 is 3-layer medical mask. The aim of this research is to modify medical purpose materials with Ag NPs and a mixture of Ag and Cu NPs to give their surface antibacterial/antiviral properties.